Micropropagation of Codiaeum variegatum (L.) Blume and regeneration induction via adventitious buds and somatic embryogenesis. - Radice, Silvia (2000)
Codiaeum variegatum (L) Blume cv. "Corazon de oro" and cv. "Norma" are successfully micropropagated when culture are initiated with explants taken from newly sprouted shoots. The establishment and multiplication steps are possible when 1 mg/L BA or 1 mg/L IAA and 3 mg/L 2iP are added to MS medium, according to the cultivar respectively selected.Adventive organogenesis and somatic embryogenesis are induced from leaf explants taken from in vitro buds of croton. On leaf-sectioned of "Corazon de oro" cultured in vitro, 1 mg/L BA stimulates continuous somatic embryos development and induces some shoots too. Replacing BA with 1 mg/L TDZ induces up to 100% bud regeneration in the same explants. On the other hand, leaf-sectioned of C. variegatum cv. Norma does not start somatic embryo differentiation if 1 mg/L TDZ is not added to the MS basal medium. Incipient callus is observed after 30 days of culture, and then, subculture to MS with 1 mg/L BA allows the same process to show on the "Corazon de oro" cultivar. Somatic embryos show growth arrest that is partially overcome by transfer to hormone-free basal medium with activated charcoal. Root induction is possible on basal medium plus 1 mg/L IBA. Plantlets in the greenhouse have variegated leaves true-to-type.